A New Strategy to Synthesize α, ω‐Dihydroxy Multiblock Copolymers via [CpRu(CH3CN)3]PF6/Quinaldic Acid Catalyst. Issue 17 (8th May 2019) - Zhu, Xiuzhong; Wang, Zichao; Liu, Jie; Min, Xin; Wang, Tong; Fan, Xiaodong
Abstract: In this study, a new strategy to synthesize random and alternating multiblock copolymers (MBCs) by the polycondensation of macromonomers' terminal hydroxyl groups with [CpRu(CH3 CN)3 ]PF6 /quinaldic acid as the catalyst is reported, which is often used for the preparation of a variety of biological small molecules via the reaction of allyl ethers. The degrees of hydroxyl functionality ( F n ) of the MBCs are assessed by titration, and the presence of hydroxyl on both the ends of MBCs is also confirmed by a chain‐extension experiment of the ring‐opening polymerization of D, L‐lactide. Abstract : α, ω‐Dihydroxy multiblock copolymers (MBCs) are synthesized via one‐pot condensation polymerization with [CpRu(CH3 CN)3 ]PF6 /quinaldic acid as a catalyst. In addition, in order to prove the universality of the synthesis of MBCs using the [CpRu(CH3 CN)3 ]PF6 /quinaldic acid catalyst, a set of MBCs synthesized with different homopolymers as macromonomers are successfully listed.